Enhanced heterojunction interface quality to achieve 9.3% efficient Cd-free Cu2ZnSnS4 solar cells using atomic layer deposition ZnSnO buffer layer - Cui, Xin (2020)
Kesterite Cu2ZnSnS4 (CZTS) photovoltaics have been comprehensively investigated in the past decades but are still hampered by a relatively large open circuit voltage (Voc) deficit, which is correlated to bulk defects in CZTS and interface recombination. Heterojunction interface management is of critical importance to tackle the interface recombination. In this work, we use atomic layer deposition (ALD) to synthesize a wide range of Zn1–xSnxO (ZTO, 0 ≤ x ≤ 1) films for application as a buffer layer in CZTS solar cells. A favorable band alignment is achieved using a 10 nm Zn0.77Sn0.23O buffer layer that enabled an impressive 10% increase in open circuit voltage of the CZTS solar cell. The microstructure and chemical nature of the CZTS/ZTO interface are carefully studied and the presence of an ultrathin Zn(S, O) tunnel layer is demonstrated. The decreased interfacial defects stemming from the minor lattice mismatch at the CZTS/Zn(S,O)/ZTO heterointerface in combination with the passivation provided by a higher sodium concentration throughout the CZTS/ZTO device explains the significant increase in open circuit voltage. Finally, we demonstrate a CZTS solar cell efficiency of 9.3%, which is the highest efficiency for Cd-free pure sulfide CZTS solar cell to date to the best of our knowledge.